Current challenges in the development and learning of the oral and written academic registers in Basque - Zabala Unzalu, Igone; Aranzabe Urruzola, Mª Jesús; Aldezabal Roteta, Izaskun (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The process of standardization and revitalization of the Basque language began in the 1970s. At that time, Basque was almost entirely relegated to private and informal settings. Since its co-officiality, the Basque language began to be used as a vehicular language in academic contexts. In the University of the Basque Country (UPV/EHU), the language is now intensively used: 74,80 % of students choose to take the entrance exam in Basque, 51 % of students undertake at least part of their undergraduate studies in Basque, and numerous Final Grade Projects, Master theses and PhD theses are carried out in Basque. Furthermore, a large number of Basque speaking students choose the elective subjects of scientific-technical communication in Basque (STCB), heirs of the subjects of Scientific Basque created in 1979 to support and guide the university community in the process of normalization of Basque. This new scenario has led to new needs: the creation of specialized terminology and phraseology was now required, as well as the elaboration of academic styles. As a result, throughout these four decades, the STCB subjects have been adapted to the needs of the standardization process, to the evolution of theoretical and applied approaches to specialized languages and terminology, and to changes in the methodological models promoted at the university. In this work, we have differentiated and characterized three phases in such adaptation. We have focused on the challenges of the current moment, which is characterized by the development of language technologies and TICs as well as the development of corpus linguistics. Corpus linguistics allows us to analyze the uses of the elements and linguistic patterns used in academic communication by experts and students, and also to evaluate the achievements and deficiencies in the development of the academic registers of the Basque language. Students access the STCB subjects in the last years of the degrees, which makes it possible to focus the learning process on linguistic awareness regarding the process of normalization of Basque, their own linguistic repertoire and the way in which each one can contribute to the development and establishment of oral and written scientific-technical registers, according to its sociolinguistic profile. The acquisition of formal oral registers and academic lexical combinations emerge as priority goals today
Keywords: Elaboration of Basque in academic contexts; oral academic registers; academic lexical combinations; language awareness